Analysis of Customer Retention Determinant Factors on Generation Z Digital Wallet Services in Indonesia - Aulia Rahmawati; Khaerunnisa Nur Fatimah Syahnur; A Mudhoffar Shaddiq Al Falah (Hasanuddin Economics and Business Review, 2024)
This study aims to identify the factors influencing customer retention in Generation Z's use of digital wallet services in Indonesia. The research uses PLS-SEM through SmartPLS 4.1.0. A total of 334 respondents from various cities in Indonesia participated in the survey. The analysis employs outer model evaluation and inner model evaluation to examine the relationships between brand image, attention to safety, consumer satisfaction, and customer retention. The findings indicate that brand image does not have a direct effect on customer retention but exerts a significant indirect effect through consumer satisfaction. Consumer satisfaction fully mediates the relationship between brand image and retention, while it partially mediates the relationship between attention to safety and retention. The strength of the mediation effect was confirmed using the bootstrapping method. These results provide valuable insights for digital wallet service providers in developing strategies to retain Generation Z users by enhancing both brand image and security features, ultimately improving consumer satisfaction.